Desquamative cheilitis in a patient with anemia of chronic : Keilitis deskuamatif pada pasien anemia penyakit kronis - Djati, Fanni Kusuma; Rahmah, Faza Faizah Nur; Sarah, Putri; Aditiyono (Makassar Dental Journal PDGI Makassar, 2025)
Anemia of chronic disease (ACD) is a normochromic normocytic anaemia that occurs in patients with chronic diseases. Desqua-mative cheilitis is a condition of persistent inflammation and sloughing of the lips. This article presents the condition of desqua-mative glossitis in a patient with ACD, along with its manifestations, pathophysiology, and management in dentistry. A 48-year-old woman came to the emergency room of Prof. Dr. Margono Soekarjo Purwokerto Hospital on 27 September 2024 with the main complaint of shortness of breath since two days ago, accompanied by cough, chest pain, fever, enlarged abdomen, full-ness, and dry lips that bleed easily. The patient had a history of uterine myoma and had been curetted. The complete blood test showed that the patient had ACD. The patient was treated with blood transfusion therapy and pharmacological medication in the form of sterile infusions, antifibrinolytic injections, antifungal, antibacterial, and mutivitamins. It was concluded that ACD is an iron deficiency condition that can cause secondary infection in the form of desquamative cheilitis, treated by increasing iron in-take and stress management.